How to manage falls in hospitalized patients: A single center experience in allogeneic stem cell transplantation setting. Issue 11 (18th March 2022) - Cioce, Marco; Lohmeyer, Franziska Michaela; Botti, Stefano; Rostagno, Elena; Orlando, Laura; Vetrugno, Giuseppe; Oppedisano, Paolo; Zega, Maurizio; Sica, Simona; Valerio, De Stefano; Bacigalupo, Andrea; Fiore, Alberto
Abstract : Abstract: In allogeneic hematopoietic stem cell transplantation (AHSCT), falls can lead to immediate and late consequences and in some cases to death. We analyzed risks and causes of falls with root cause analysis (RCA) based on which improvement interventions were implemented. A retrospective observational study was conducted to analyze with RCA data of incidence reports and medical records of patients admitted; an expert panel identified actions to prevent falls, which were collected in a checklist. Between December 2017 and November 2019, 214 patients were admitted to ordinary hospital stays for AHSCT or AHSCTrelated complications. In this period, 15 falls, involving 11 patients, occurred resulting in a 2.32 d/patient incidence. In 66.67% of cases minor head trauma occurred. Diuretic drugs (93.33%), induced hyper-diuresis in nonbladder catheter patients (93.33%) and antihypertensive drugs (93.33%) were reported as most common cause in our incident reports. The most frequent fall time slot was between 10 PM and 7 AM (60%). We determined with RCA diuretics and consequent induced hyper-diuresis (80%), self-insufficiency (40%), antihypertensive (33.3%) and noncompliance (33.3%) as the most common cause of falls. Finally, 16 actions, collected in a "safe comfort" checklist, were identified to prevent falls. Diuretic drugs inducing hyper-diuresis, self-insufficiency, poor patient compliance, orthostatic hypotension, fever, night-time and obstacles within inpatient units are the most common contributing factors. Therefore, administration of diuretic and antihypertensive drugs should be rescheduled and a multidimensional risk assessment scale integrated with a preventive action plan, such as the safe comfort checklist, should be implemented to reduce falls.